The relationships between portuguese banks and their customers in a recessionary context - Nunes, Paulo Filipe Figueiredo (2015)
Financial institutions were in the genesis of the crisis that led to the current recession. This dissertation aims to understand better the relationship Portuguese people have with their banks in a recessionary context, to provide knowledge that may contribute to the Marketing field of research and to the Banking industry. Having that purpose in mind, a quantitative study was conducted using data gathered by questionnaire using a sample of 488 respondents, which was further complemented by the information collected applying Netnography. The overall analysis suggests that the impact of the crisis on the household financial situation throughout the last couple of years influences attitudes towards money and expenses. The way customers’ purchase and consumption behaviors were affected by crisis are, to some extent, positively related to the satisfaction with the main bank. From the Relationship Marketing constructs addressed, only two are important to explain customer loyalty in a recessionary context, implying that marketing researchers and practitioners might need to adapt their conducts according to the economic conjuncture.